Aspects of microbially induced corrosion papers from EUROCORR '96 and the EFC Working Party on Microbial Corrosion - Thierry, D. (Publications (European Federation of Corrosion) ;, 1997)
This volume contains 11 chapters representing reports made in the MIC session at EUROCORR '96 together with a paper from the Working Party on the economics of MIC in relation to power station performance. Much attention is given to the currently important subject of biofilms, particularly on stainless steel in seawater. There are descriptions of the characterisation of biofilms and their effects. The volume concludes with an account of biological effects in power stations, the economic implications and prevention methods.